2012
DOI: 10.1097/aud.0b013e31824c0935
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Noise Exposure During Solitary Trumpet Playing

Abstract: During solitary play, trumpeters generate noise levels that temporarily decrease DPOAE amplitudes and that by themselves have the potential to result in permanent noise-induced hearing loss. Trumpeters who practice/perform over a period of years should be concerned about the implications of their craft on their hearing and should be offered personalized hearing conservation programs. The use of earplugs offers a practical and cost-effective means of hearing protection and, for this group of trumpeters, did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
(46 reference statements)
0
10
0
1
Order By: Relevance
“…It has previously been found that specific sessions of music exposure led to reductions in college music students’ OAE amplitudes when measured within 2-10 min after the exposure. [ 6 8 ] In another previous study, however, no abnormalities in TEOAE amplitudes were found among university marching band members. [ 7 ] None of these previous studies included a control group to determine whether the music students’ OAEs differed from those of nonmusic students.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…It has previously been found that specific sessions of music exposure led to reductions in college music students’ OAE amplitudes when measured within 2-10 min after the exposure. [ 6 8 ] In another previous study, however, no abnormalities in TEOAE amplitudes were found among university marching band members. [ 7 ] None of these previous studies included a control group to determine whether the music students’ OAEs differed from those of nonmusic students.…”
Section: Discussionmentioning
confidence: 90%
“…Music students’ data collection sessions were rescheduled if they had been playing or rehearsing within the previous hour, based on previous research that found that DPOAE amplitudes recovered within less than 1 dB of prerehearsal levels within that timeframe. [ 8 ] It was also not possible to allow a longer interval for the music students because of the many hours per week that they spent rehearsing. Music majors were also queried regarding their primary instrument, number of years they had been playing an instrument, and approximate total hours per week spent practicing individually and in ensembles, bands, and orchestras.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations